Linguistic theory of Deixis: classical and modern views - Negmatova, Mumtozbegim Ulugbek qizi; Bayjanova , Okila Iskandarovna (The Lingua Spectrum, 2026)
This article studies the theories of the phenomenon of deixis, lists the main points of research on the emergence of this term and its research to date. Also, classical and modern views on the types of deixis are studied and analyzed using the comparative-historical method. The first hypotheses about deixis and who later studied it are studied. The work carried out in this area, the emergence of deixis, their role in linguistics, what types there are and the importance of studying their types are also discussed, and research in this area will be very useful for researchers. This is because the study of deixis serves as the basis for the fields of pragmatics, cognitive linguistics and linguoculturology in modern linguistics. The expression of deixis through paralinguistic means was also discussed, and their importance in the speech process was discussed. The difference between deixis and anaphora has not been resolved to this day, and the similarities and differences between the two concepts were compared. We can say that the importance of studying the phenomenon of deixis has been explored in all aspects.